Sprint running development: Examining 100 meters performance between Spanish and French athletes from junior to senior categories - Agudo-Ortega, A.; Salinero, J. J.; Rodriguez-Barbero, S.; Valero, F.; Gonzalez-Rave, J. M. (9th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Human development is a messy, complex, and difficult road to predict. At an early age, growth, maturation, and development occur simultaneously and influence physical activity, fitness, and performance (1), however, in the sports domain, the development of athletes will be strongly determined by favourable environments (2). To date, no study has analysed the differences in terms of sprint performance across categories between countries. The objective of our study is to compare the progression of marks from junior (U16 and U20) to senior categories between two different European countries. METHODS: An observational and longitudinal analysis was carried out using the Spanish Athletics and French Athletics Federations database rankings. We analysed the top 25 marks from 100 meters sprint running athletes (1523 recorded marks; 757 females and 766 males) from U16, U20 and senior categories who have been recorded between 2015 and 2019. A two-way ANOVA (country x category) was used to analyse the differences between Spanish and French sprint athletes` marks. Effect sizes (ES) were calculated by using the Cohen`s d (< 0.01) between countries and categories. There were significant differences between countries both in males and females in U16 (p = 0.017 in females and p < 0.01 in males), in U20 (p < 0.01 in females and males) and the senior category (p < 0.01 in females and males). However, this difference increased from a small effect size at U16 (0.30 females; 0.58 for males) to moderate at U18 (0.82 for females and 1.08 males), and large at the senior stage (1.55 females, 1.49 males). CONCLUSION: Data between Spanish and French sprint running athletes show significant differences between all categories from U16 onwards. Although the results showed significant differences in all categories, the effect size increases as athletes progress through the categories widening the gap between countries. These results reinforce the idea that national sports systems might play an important role in long-term athletes` development.